Optimizing the Integrated Farming System of Coffee and Goat to Maximize Farmers' Income in North Sumatra, Indonesia - Dinda Aslam Nurul Hida; Dwi Rachmina; Amzul Rifin (Agro Bali : Agricultural Journal, 2023)
Most coffee farmers in North Sumatra still need to implement an integrated coffee and goat cultivation system. Only 0.2% of farmers have implemented the program. An integrated farming system cannot be implemented due to limited resources, and optimal conditions for an integrated farming system for coffee plants and goat livestock in North Sumatra have yet to be found. Therefore, this study aims to determine the optimal conditions for an integrated farming system for coffee plants and goat livestock to maximize farmers' income. The sample size is six farming units spread across three districts: Simalungun, North Tapanuli, and Karo districts in North Sumatra Province. Quantitative analysis using a linear programming model was carried out computationally with the help of LINDO 6.1 software. The study results show that the revenue for the optimal solution from the integration model generates IDR 169,358,700.00, 1.04% higher than the actual income. This was due to an increase in coffee bean productivity to 1.68 tons.ha-1 per year with a simple shading coffee pattern, namely coffee planting with a cover crop of 300 trees per ha, as well as an increase in the number of goats kept. , from the actual condition of 59.33 goats to 117 goats. Farmers are advised to utilize all products between coffee and goat farms as their respective production inputs and not sell intermediate products.